RAGAM BAHASA UPDATE STATUS FACEBOOK Analisa Wacana Studi Kelompok Mio Salatiga Club Automatic Leader - Intan Duhita; Daru Purnomo; Rulliyanti Puspowardhani (Cakrawala Jurnal Penelitian Sosial, 2013)
Human are creatures of language, they use language as communication and allways use language, language can get idea, and wish in tho say the opinion and information. Human being as a society have communication and doing interaction use language, so language is a communication. Human have a lot of for communication, one of them is internet, internet like facebook. As human society, human want to do sociality and communication with them.  In communication process a people who have interaction in it must to want say a massage in order to the message can be understood by other people. Language is sign sound that is agreement to used by the member of society in corporation communication and identification.This study aims to describe the language style status updates on facebook and meaning of language status updates on facebook. This study will use qualitative research methods. The unit of observation to be examined is in facebook. The unit of analysis is to analyze the elements of communication such as words, paragraphs, themes and events that are coded to be performed generalization. This study will observe the update status of the motor in the Salatiga Mio. Quest for the meaning of the data analysis will be done by performing data collection, data reduction, data presentation, and verification.The results showed that this language update status facebook happened because there is no convention which role the way to write update status. Beside that, the factor like creativity, trend and the individu writer types. Update status facebook have big influence the models of update status facebook writing. Keywords: updates status facebook, style, the meaning of language, discourse analysis